2016
DOI: 10.1093/jee/tow147
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-Optimized Sequential Sampling Plan for Cabbage AphidsBrevicoryne brassicaeL. (Hemiptera: Aphididae) in Canola Fields

Abstract: The cabbage aphid is a significant pest worldwide in brassica crops, including canola. This pest has shown considerable ability to develop resistance to insecticides, so these should only be applied on a "when and where needed" basis. Thus, optimized sampling plans to accurately assess cabbage aphid densities are critically important to determine the potential need for pesticide applications. In this study, we developed a spatially optimized binomial sequential sampling plan for cabbage aphids in canola fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…While straightforward strategies of applying insecticides at pre-determined times may be preferred, over integration of multiple control methods, by growers due to their operational simplicity and perceived effectivity 42 , such approaches are likely to fail in the absence of action threshold guidelines 43 . Action threshold based guidelines have been developed for cruciferous pests 44 but thresholds can vary according to pest species (e.g. due to differing consumption rates) 41,45 and may also differ regionally 46 .…”
Section: Discussionmentioning
confidence: 99%
“…While straightforward strategies of applying insecticides at pre-determined times may be preferred, over integration of multiple control methods, by growers due to their operational simplicity and perceived effectivity 42 , such approaches are likely to fail in the absence of action threshold guidelines 43 . Action threshold based guidelines have been developed for cruciferous pests 44 but thresholds can vary according to pest species (e.g. due to differing consumption rates) 41,45 and may also differ regionally 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased performance (less sampling needed) of such a spatially targeted sampling approach was demonstrated for the wheat stem sawfly ). In addition, Severtson et al (2016) described a spatially optimized sequential sampling plan for cabbage aphids in canola fields. In their study, canola fields were divided into two types of sampling grids: inner grids and edge grids.…”
Section: Potential Applications Of Edge-biased Distributions Into Insmentioning
confidence: 99%
“…Their sampling results showed that 9 out of 20 edge grids displayed infestation level above threshold while only 2 out of 20 inner grids showed infestation level above threshold. Taking the proposed edge effect distribution of aphids into account, Severtson et al (2016) conducted stratified sampling analysis and managed to reduce spatial variability as well as to increase accuracy of infestation level. Nonetheless, we also acknowledge that edge effect distribution of insects in many agricultural systems can be highly seasonal and temporally dependent (Corbett and Rosenheim 1996;Winder et al 1999;Holland et al 1999;Wilson and Morton 1993).…”
Section: Potential Applications Of Edge-biased Distributions Into Insmentioning
confidence: 99%
“…This results in a variable number of samples in sequential sampling plans . Therefore, in sequential sampling plans, the number of evaluated samples, the time and the cost of sampling may be lower than those in conventional plans . Nevertheless, the use of a certain sequential sampling plan in any given crop must be validated.…”
Section: Introductionmentioning
confidence: 99%